YouTube™ as a source of information for Candida auris infection: a systematic review - Jiangqing Huang; Shengcen Zhang; Qirong Xiao; Yingping Cao; Bin Li (BMC, 2020)
Abstract Background Candida auris is a novel Candida species, and has emerged globally as a multidrug-resistant health care-associated fungal pathogen. YouTube™ ( http://www.youtube.com ) as the largest free video-sharing website is increasingly used to search health information. Thus, the aim of this study was to evaluate the content, reliability and quality of YouTube™ videos regarding Candida auris infection, and to identify whether it is a useful resource for people. Methods The YouTube™ was used to search systematically for videos using the keywords: "Candida auris infection" and "Candida auris". Strict inclusion and exclusion criteria were used to select the videos. The videos were reviewed and scored by two independent reviewers and recorded the "title", "length", "views", "comments", "dislike", "like", "posted days" and "category of videos". The videos were categorized as "poor", "good" and "excellent" by the score. The DISCERN tool was used to assess the reliability of the YouTube™ videos. Results Seventy-six videos were included in final analysis in our study. Most videos (59.2%, 55/76) had better quality. There were no statistically significant differences between groups in respect of the number of likes, dislikes, views, comments, percentage positivity, likebility, view rate and viewers' interaction. Length and posted days were significantly associated with the classification. The videos were categorized as "educational video", "new report", "personal experience and blog entertainment" and "interview". Significant differences were found in the source of videos and the characteristics of the individuals appearing in a video between the groups. Conclusion YouTube™ has striking potential to be an effective user-friendly learning interface for people to obtain information of Candida auris infection.